Analysis of the Role of Advocates in Industrial Relations Dispute Resolution: The Case of the Medan Manpower Office - Limutra, William Leonardy; Siregar, Taufik; Ramadhan, M. Citra (Journal of Public Representative and Society Provision, 2024)
Industrial relations dispute resolution is an important issue in the world of labor that requires the right legal approach. This study aims to analyze the role of advocates in resolving industrial relations disputes at the Medan City Manpower Office, especially in the mediation and litigation stages. The research method used is a qualitative approach with data collection through in-depth interviews, observations, and document studies. The data were analyzed descriptively by relating them to relevant theories and legal frameworks. The results of the study show that advocates have a strategic role in helping the parties to the dispute understand their rights and obligations, both through legal consultation, assistance in mediation, and legal representation in the litigation process at the Industrial Relations Court. In addition, advocates also contribute to the preparation of legal documents that support client claims. However, there are a number of obstacles faced by advocates, such as low legal understanding from the parties to the dispute, limited competence of mediators, and lack of supporting evidence. This obstacle often prolongs the duration of dispute resolution and reduces the effectiveness of mediation. This study concludes that the role of advocates is very important in creating a fair and efficient dispute resolution process. However, improvements are needed in the dispute resolution system, such as increasing legal literacy, training mediators, and optimizing mediation procedures. This finding is expected to contribute to the development of better industrial relations settlement practices, especially in the city of Medan.